Արտո Չաքմաքչյանի գծանկարչությունը - Շուշան Վարդանյան (ՀՀ ԳԱԱ հրատ.)
Arto Chakmakchian’s graphic art, one of the interesting domains of his creation requires thorough study. For some sculptures their graphic works are subsidiary taking shape in the earlier stages of their creative work, when concepts are originated and formed, and they are in search of their own unique style and modes of creation. Graphic art is an absolutely independent sphere for many masters of international fame. However, Chakmachian has graphic pieces, witnessing his creative explorations as well as pieces presenting great value in theirown right in fine art. Chakmakchian has throughout the years created a rich, multifaceted and extraordinary gallery of events, situations, occurrences, different phenomena, of simple, famous and dear persons, as well as remarkable intellectuals: Narekatsi, Komitas, Kostan Zaryan, Avetik Isahakyan, Ervad Kochar, Minas Avetisyan, Tigran Mansuryan, etc.Графика Арто Чакмакчяна требует досконального изучения, однако можно сказать, что она является одним из уникальных аспектов творчества художника. Для некоторых художников графика играет второстепенную роль и проявляется на ранних стадиях их работы, когда творческие идеи только-только рождаются, когда художники находятся в поисках своего собственного уникального стиля творчества. У других мировых мастеров графика является основным видом самовыражения. В графике Чакмакчяна есть работы, которые являются отражением его творческих поисков, а также работы, которые являются художественными ценностями. На протяжении многих лет он создал богатую и многогранную галерею известных и любимых лиц, интеллектуалов и простых людей: Нарекаци, Комитас, Костан Зарьян, Аветик Исаакян, Ерванд Кочар, Минас Аветисян, Тигран Мансурян и др.
Keywords: Fine Arts; Painting